2006
DOI: 10.1016/j.bmc.2006.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics and antimicrobial activity of traditional stoned table olives ‘alcaparra’

Abstract: Abstract-In the present work, we report the determination of phenolic compounds in 'alcaparra' table olives by reversed-phase HPLC/DAD, and the evaluation of their extract in vitro activity against several microorganisms that may be causal agents of human intestinal and respiratory tract infections, namely Gram positive (Bacillus cereus, Bacillus subtilis, and Staphylococcus aureus), Gram negative bacteria (Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumoniae) and fungi (Candida albicans and Cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 28 publications
7
85
1
3
Order By: Relevance
“…Daviana cultivar proved to be the most promissory cultivar, presenting the best results, with higher growth inhibition zones and lower MICs. Fruit extracts had a similar antimicrobial activity to hazel leaf extracts for the same cultivars (Oliveira et al, 2007) which were effective at low concentrations (around 0.1 mg/mL); the present extracts are even better than table olive extracts previously studied by us Sousa et al, 2006). The antimicrobial agents added in food generally present problems related to some inherent toxicity (resistance, mutagenesis and carcinogenesis effects, for example) and natural compounds, such polyphenols have gained increasing importance.…”
Section: Antimicrobial Activitymentioning
confidence: 49%
See 2 more Smart Citations
“…Daviana cultivar proved to be the most promissory cultivar, presenting the best results, with higher growth inhibition zones and lower MICs. Fruit extracts had a similar antimicrobial activity to hazel leaf extracts for the same cultivars (Oliveira et al, 2007) which were effective at low concentrations (around 0.1 mg/mL); the present extracts are even better than table olive extracts previously studied by us Sousa et al, 2006). The antimicrobial agents added in food generally present problems related to some inherent toxicity (resistance, mutagenesis and carcinogenesis effects, for example) and natural compounds, such polyphenols have gained increasing importance.…”
Section: Antimicrobial Activitymentioning
confidence: 49%
“…There is growing interest in using natural antimicrobial compounds because of consumer's pressure on the food industry to avoid chemical preservatives and of the increasing resistance to antibiotics. With this regard the antimicrobial capacity of phenolic compounds has also been reported (Rauha et al, 2000;Puupponen-Pimiä et al, 2001;Proestos et al, 2005;Sousa et al, 2006;Pereira et al, 2006Pereira et al, , 2007. In fact, there are recent reports about the antioxidant and antiradical activities in extracts of Turkish hazelnut kernel, hazelnut green leafy cover (Alasalvar et al, 2006b), and other hazelnut byproducts such as hazelnut tree leaf (Oliveira et al, 2007;Shahidi et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Its absence in the pulp of olives could be related to its sensitivity to phenolic compounds and to low value of a w . In fact previous works Sousa et al, 2006Sousa et al, , 2008 proved that olive pulp is rich in phenols that showed antimicrobial activity. C. glabrata and C. krusei have emerged as important pathogens, whose clinical isolates have been increasing, being C. glabrata associated, specially, to urinary tract, mucosal areas and lungs (Hazen, 1995).…”
Section: Isolation and Identification Of Yeastsmentioning
confidence: 91%
“…Several of these compounds had excellent antibacterial activities also against Vibrio cholera (Martini et al, 2004b). Some mechanisms of antimicrobial activity of phenolic compounds includes their ability to denature microbial proteins as surface-active agents (Sousa et al, 2006). Phenolic compounds may also react with cellular membrane components and impair the function and integrity of cells (Raccach, 1984).…”
Section: Antimicrobial Assaymentioning
confidence: 99%